Keloid Patient Plasma-Derived Exosomal hsa_circ_0020792 Promotes Normal Skin Fibroblasts Proliferation, Migration, and Fibrogenesis via Modulating miR-193a-5p and Activating TGF-β1/Smad2/3 Signaling - Hu H; Mao G; Zheng J; Guo F (Dove Medical Press, 2022)
Huan Hu,* Guangyu Mao,* Jianghong Zheng, Feng Guo Department of Plastic Surgery, Shanghai Sixth People's Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, 200233, People's Republic of China*These authors contributed equally to this workCorrespondence: Jianghong Zheng; Feng Guo, Department of Plastic Surgery, Shanghai Sixth People's Hospital Affiliated to Shanghai Jiao Tong University School of Medicine, 600 Yishan Road, Xuhui District, Shanghai, 200233, People's Republic of China, Email JianghongZheng2016@126.com; gfasph@163.comBackground: Keloids are fibroproliferative disorders, which seriously affect the quality of life of patients with keloids. Additionally, circRNAs are enriched within exosomes derived from human blood samples, whereas their relationship with keloids remains largely unknown. It has been reported that hsa_circ_0020792 was abnormally upregulated in keloid tissues. However, the role of keloid patient plasma-derived exosomal hsa_circ_0020792 in the formation and development of keloids is not well understood.Methods: Exosomes were isolated from the peripheral blood plasma of the patients with keloids (keloid patient-Exo) and healthy controls (Healthy control-Exo). The hsa_circ_0020792 and miR-193a-5p levels in keloid patient-Exo and healthy control-Exo, as well as in keloid fibroblasts and normal skin fibroblasts (NFs) were evaluated by RT-qPCR.Results: The level of hsa_circ_0020792 was remarkably increased in keloid patient-Exo and keloid fibroblasts compared with that in Healthy control-Exo and NFs, respectively. In addition, keloid patient-Exo obviously enhanced the viability, migration, and extracellular matrix (ECM) synthesis, but reduced the apoptosis of NFs. Moreover, keloid patient-Exo notably promoted the fibrogenesis of NFs, as characterized by enhanced TGF-β signaling, increased expressions of phosphorylated Smad2/3. However, downregulation of hsa_circ_0020792 markedly reversed the promoting effects of keloid patient-Exo on cell growth, migration, and myofibroblast activation and fibrogenesis. Furthermore, downregulation of hsa_circ_0020792 significantly reduced the viability, migration, and fibrogenesis in NFs, whereas these phenomena were reversed by miR-193a-5p inhibitor.Conclusion: Collectively, keloid patient plasma-derived exosomal hsa_circ_0020792 could promote the proliferation, migration, and fibrogenesis of NFs via modulating miR-193a-5p and activating TGF-β 1/Smad2/3 signaling.Keywords: keloid, fibroblasts, exosomes, hsa_circ_0020792, miR-193a-5p